Splenocyte membrane changes and immunosuppression during infection and reinfection with trypanosoma cruzi - Serrano, León; O Â´Daly, José (Investigación Clínica, 2013)
Antisera to epi- and trypomastigote forms of Trypanosoma cruzi were used to detect trypanosome antigens on the surfaee of lymphocytes from infected miee. Only the antitrypomastigote serum could recognize antigens expressed transiently on the splenocyte membranes from infected animals. The number or struetural configuration of Concanavalin A receptors was similarly affected and a clear correlation was seen between these two types of membrane changes and the immunosuppression to mitogens and SRBC presented by the infected mice. Reinfected animals did not show evidences of trypanosome proliferation in blood or tissues nor trypomastigote antigens on splenocytes, but presented a less intense, transient immunosuppression as measured by responsiveness to mitogens and SRBC. suggesting that the primed immune system can eliminate the new parasite inoculum before the host is immunosuppressed and also that the liberation of strong immunosuppressor trypomastigote antigens induce the new state of suppression.